Students’ Motivation in Speaking English: Motivasi Siswa dalam Berbicara Bahasa Inggris - Ihsan, Mas Darul (JEES (Journal of English Educators Society), 2016)
Motivation is a concept without physical reality, we cannot see motivation; we see effort, interest, attitude and desire. For speaking, it is important first to give competence and then performance. Competence is more likely to the extent a communicator is motivated to be so. Motivation is the extent to which a communicator is drawn towards or pushed away from communicating competently in a given context then performed. This is a descriptive quantitative research. The data obtained from the questionnaire distributed and analyzed to get the result. The date taken from the students of Muhammadiyah 1 Senior High School Gresik in Easy-Speaking course. The researcher wanted to know the students’ motivation in practicing speaking English in Easy-Speaking course. The results show that 1) the learners effort in practicing speaking English is 56.1 %. 2) The learners’ interest in practicing speaking English is 49.7 %. 3) The learners’ attitude towards practicing speaking English is 59.9 %. 4) The learners’ desire in practicing speaking English is 71.43 %. Then, some suggestions are made: 1) Using media is very important both to increase the learners’ motivation and to give a big opportunity to learners to explore their idea. 2) Giving more variations techniques in teaching and learning process in order do not monotonous. 3) Giving prizes, encouraging and giving extra points for learners who can express their idea by speaking English well. 4) Creating favorable atmosphere in the classroom.